Autohton și contemporan. „Amurgul burghez” la Târgu-Mureș în 1983 - György, Andreea (Theatrical Research, 2021)
Autochtonous and Contemporary. The "Bourgeois Twilight" on Stage in Târgu-Mureș in 1983 Friday, 4 February 1983, spectators gathered for the premiere of Târgu-Mureș National Theater’s Hungarian department. The performance entitled "Egy öngyilkos világa", was directed by Dan Alecsandrescu, and based on the drama signed by an autochthonous and even local author, Romulus Guga: "Amurgul burghez" ("The Bourgeois Twilight"). The analysis of this theatrical event shows the evolution of the interpretation of the contemporary local drama in the Ceausescu period. I reviewed the semantic changes of the term and I examined how they affected the repertoire of the theater from Târgu-Mureș in that time.